Morphology of Anterolateral Ligament: A Cadaveric Study and Its Implications for Knee Reconstructive Surgery - Anita Rahul Gune; Aryan Rahul Gune (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
Background: The anterolateral ligament (ALL) arises from the lateral epicondyle of the femur and attaches to the tibia between Gerdy’s tubercle (GT) and the fibula head. The ALL is a ligamentous tissue that gets taut when the tibia rotates 30 degrees medially. It has been suggested that the ALL of the knee plays an important role in reducing rotational instability and that reconstruction of the ALL, together with the anterior cruciate ligament (ACL), may avoid a persistent pivot shift after surgery. Aims: The primary goal of the study was to identify the structure that appeared to be controlling anterolateral rotation, characterise its dimensions and attachments, and interpret them in the context of previous work. Study Design: This is a Cadaveric dissection study. Place and Duration of Study: From 2016 to 2018, this study was carried out at the Department of Anatomy, D.Y. Patil Medical College in Kolhapur. The ALL was found in 14 female and 16 male cadavers, with a total of 60 knee joints. Methodology: The ALL tissue was discovered by rotating the tibia inside. A digital caliper was used to take measurements, and the origin and insertion points were recorded. The ALL was detected with mean dimensions of 38.06 ± 3 mm on right side and 37.94 ± 3 mm on the left side, width 4.38 ± 0.25 mm on right side and 4.37 ± 0.25 mm on left side, and thickness 0.9 ± 0.02 mm on both sides. The femoral origin is Posterior and Proximal (PP) in 23, Anterior and Distal (AD) in 29, and Femoral Lateral Epicondyle in eight knee joints. The tibial insertion measured 1.79 ± 0.3 mm on the right side and 1.82 ± 0.3 mm on the left side from Gerdy’s tubercle (GT), and 1.28 ± 0.03 mm from the fibula head (FH). Results: The ALL was identified in 14 females and 16 males cadavers, total 60 knee joints. This study’s findings are consistent with previous research indicating that ALL is a capsular thickening with meniscus attachment. Conclusion: The data will assist surgeons in performing reconstructive surgery and selecting the most appropriate graft. Furthermore, this ligament should be included in all gross anatomy textbooks so that medical undergraduates are aware of ALL.